Circulating tumour DNA reveals genetic traits of patients with intraductal carcinoma of the prostate. (3rd August 2021) - Zhao, Jinge; Sun, Guangxi; Zhu, Sha; Dai, Jindong; Chen, Junru; Zhang, Mengni; Ni, Yuchao; Zhang, Haoran; Shen, Pengfei; Zhao, Xiaochen; Zhang, Bei; Pan, Xiuyi; et al.
Abstract : Objectives: To investigate the genetic alterations of patients with prostate cancer (PCa) with and without intraductal carcinoma of the prostate (IDC‐P). Patients and Methods: We performed targeted sequencing of plasma cell‐free DNA on 161 patients with prostate adenocarcinoma (PAC) with IDC‐P and 84 without IDC‐P. Genomic alterations were compared between these two groups. The association between genetic alterations and patients' survival outcomes was also explored. Results: We identified that 29.8% (48/161) and 21.4% (18/84) of patients with and without IDC‐P harboured genomic alterations in DNA repair pathways, respectively ( P = 0.210). Pathogenic germline DNA repair alterations were frequently detected in IDC‐P carriers compared to IDC‐P non‐carriers (11.8% [19/161] vs 2.4% [two of 84], P = 0.024). Germline BReast CAncer type 2 susceptibility protein ( BRCA2 ) and somatic cyclin‐dependent kinase 12 ( CDK12 ) defects were specifically identified in IDC‐P carriers relative to PAC ( BRCA2 : 8.7% [14/161] vs 0% and CDK12 : 6.8% [11/161] vs 1.2% [one of 84]). Patients with IDC‐P had a distinct androgen receptor (AR) pathway alteration, characterised by an enrichment of nuclear receptor corepressor 2 ( NCOR2 ) mutations compared with patients with pure PAC (21.1% [34/161] vs 6.0% [five of 84], P = 0.004). Increased AR alterations were detected in patients harbouring tumours with an IDC‐P proportion of ≥10% vs those with an IDC‐P proportion of <10% (6.4% [five of 78] vs 18.1% [15/83], P = 0.045). For IDC‐P carriers, tumour protein p53 ( TP53 ) mutation was associated with shorter castration‐resistant‐free survival (median 10.9 vs 28.9 months, P = 0.026), and BRCA2 alteration was related to rapid prostate‐specific antigen progression for those receiving abiraterone treatment (median 9.1 vs 11.9 months, P = 0.036). Conclusion: Our findings provide genomic evidence explaining the aggressive phenotype of tumours with IDC‐P, highlighting the potential therapeutic strategies for this patient population.